Laser-chemical activation of alumina ceramics surface - Smirnov S. V. (2005, 2005)
The study of the process of laser-chemical activation of ceramic surface and its subsequent chemical metallization is described. The obtained results serve as the basis for the development of an industrial method for local metallization of the surface of products made of alumina ceramics